Strategi Penerjemahan Gaya Bahasa Figuratif dalam Novel Lelaki Harimau: Kajian Stilistika Indonesia–Inggris: Translation Strategies of Figurative Language Style in the Novel "Lelaki Harimau": An Indonesian–English Stylistic Study - Fardeni, Haekal; Maulina, Intan (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze translation strategies for figurative language in Indonesian literary works into English, using a stylistic approach and translation theory. The main focus of the study is how translators maintain the meaning, aesthetic effects, and cultural context of the source text without sacrificing the beauty of the language in the target text. This study uses a qualitative descriptive method with content analysis techniques on a number of figurative language style sentences found in selected literary works. The results show that the most frequently used translation strategies are equivalence, adaptation, and paraphrase. These three strategies have proven effective in maintaining the aesthetic and emotional value of the source text, though in some cases, shifts in meaning arise due to cultural and linguistic differences between the two languages. Numerically, the stylistic analysis reveals that metaphor is the most frequently used figurative device, accounting for 36% of all stylistic findings. This finding confirms that figurative language style not only functions as linguistic ornamentation but also represents the author's complex cultural values, imagination, and emotional expression. Therefore, translators need to be sensitive to stylistic elements and cultural contexts to produce communicative translations while remaining faithful to the original meaning and nuances of the source text. This research is expected to enrich the study of literary translation in Indonesia and to serve as a reference for researchers and translators in understanding the challenges of translating figurative language across cultures.